Tall tail : [large type] a Mrs. Murphy mystery - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Brown, Rita Mae. Mrs. Murphy mystery., 2016)
"Returning to Virginia's post-revolutionary history and to characters introduced in Tail Gait, the story follows the Garth sisters and their husbands, neighbors to a brutal slaveholder whose murder at the hands of one of his slaves is neither unexpected nor unwarranted, especially when the impetus was an attack on that slave's wife. The sisters manage to smuggle the fugitive to safety in York, Pennsylvania, while ensuring that the circumstances underlying the entire ordeal stay long buried. Until now. Harry and her animal companions come closer to drawing a link between the past and the present. And in this centuries-spanning caper, they will discover that hiding who you really are may have mortal consequences. "--